Investigation of the physico-chemical properties and flotation ability of the developed experimental batches of composite chemical flotation reagentsfoamers KHF-VS-B (Международный научный журнал «Инженер», 2026)
Flotation enrichment is one of the key stages in the processing technology of non-ferrous and precious metalores. The efficiency of this process is determined by the physicochemical interactions occurring in the liquidphase and on the surface of the minerals. In the aqueous medium, where the separation of mineral particlestakes place, a gaseous phase—air bubbles—exists alongside the solid phase, playing a crucial role in theflotation process. In this context, to identify the flotation capacity of the developed flotation reagentsfoamingagents, it is necessary to study their physicochemical properties, which make it possible todetermine their flotation performance. Accordingly, the aim of this work is to investigate thephysicochemical properties and flotation capacity of the experimental batches of the composite chemicalflotation reagents-foaming agents КХФ-ВС-Б.